Seroepidemiology for Orthorubulavirus suis in Mexican Pigs by Development of an Indirect ELISA Based on a Recombinant NP Protein - Rocío Lara-Romero; José Luis Cerriteño-Sánchez; María Azucena Castañeda-Montes; Humberto Ramírez-Mendoza; Julieta Sandra Cuevas-Romero (Pathogens)
Orthorubulavirus suis (LPMV) is the etiologic agent of blue eye disease (BED), which affects pigs of all ages, and it has been endemic in central Mexico since the 1980s. To date, no disease control program has been established. Therefore, there is a need for a serological diagnostic method with high sensitivity and specificity. In this study, the recombinant protein NP of LPMV was produced in the E. coli BL21 system and then purified using affinity chromatography. The purified protein was used to coat plates for an indirect ELISA assay (iELISA). To determine the sensitivity and specificity of the test, a 2 × 2 contingency table was constructed using positive and negative control sera. The specificity and sensitivity levels were 98.1% and 98.7%, respectively. According to our findings, 45% of serum samples (378/839) were positive, with seropositivity percentages in the analyzed states ranging from 72.5% to 6%. To confirm the presence of antibodies, the indirect immunofluorescence technique was applied to iELISA-positive serum samples. In this study, antibodies against the LPMV nucleoprotein were detected, indicating that the virus or defective particles may be circulating in Mexican pigs and highlighting the risk of LPMV spreading to disease-free areas.